Defect tolerance and hydrogen susceptibility of the fatigue limit of an additively manufactured Ni-based superalloy 718. (October 2020) - Kevinsanny,; Okazaki, Saburo; Takakuwa, Osamu; Ogawa, Yuhei; Funakoshi, Yusuke; Kawashima, Hideto; Matsuoka, Saburo; Matsunaga, Hisao
Highlights: Fatigue strength properties of an additively-manufactured alloy 718. Competition between defect size and grain size in determining the fatigue limit. Successful evaluation of the defect tolerance as a small crack problem. Experimental finding of the harmlessness of solute hydrogen on the fatigue limit. Abstract: The sensitivity of the fatigue limit of an additively manufactured, Ni-based superalloy 718 sample to surface finishing conditions and solute hydrogen was investigated via a series of tension–compression fatigue tests. The results revealed that neither defects nor hydrogen diminished the fatigue limit of the sample. The high defect tolerance of this material is attributed to a large unit of crack initiation in the coarse grain, which eclipses the detrimental effect of AM-process-induced defects. Also, from the results, it is inferred that hydrogen has little effect on the crack propagation rate and the crack growth threshold of the material.